2018
DOI: 10.21059/buletinpeternak.v42i1.22313
|View full text |Cite
|
Sign up to set email alerts
|

Carcass Quality, Non-Carcass Component and Meat Cholesterol of Kacang Goat Fed with Fermented Cocoa Shell

Abstract: The experiment was conducted to investigate carcass quality, non-carcass component and meat cholesterol content of Kacang goat fed with fermented cocoa shell (FCS). Materials used in the experiment consisted of 9 male Kacang goat (6 - 9 months of age and ± 18,67 kg of body weight), corn straw, rice bran and FCS using three types of starters. The goat was divided into 3 groups of FCS fermentation of cocoa shell were carried out using 3 types of starters, i.e. cocoa shell fermentation 1) without additional start… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
1
1
Order By: Relevance
“…Cholesterol, in this study, was higher than the report of Suryanto et al [29] that obtained cholesterol ranging from 30.13 to 34.96 mg/100 g in Kacang goats given fermented cocoa skin, but lower than the report of Mirdhayati et al [17] that obtained cholesterol in Kacang goat meat ranged from 112 to 256 mg/100 g. Cholesterol levels can differ between livestock, and this difference can be caused by differences in food type, age of livestock, and management [29].…”
Section: Cholesterol Contentcontrasting
confidence: 81%
“…Cholesterol, in this study, was higher than the report of Suryanto et al [29] that obtained cholesterol ranging from 30.13 to 34.96 mg/100 g in Kacang goats given fermented cocoa skin, but lower than the report of Mirdhayati et al [17] that obtained cholesterol in Kacang goat meat ranged from 112 to 256 mg/100 g. Cholesterol levels can differ between livestock, and this difference can be caused by differences in food type, age of livestock, and management [29].…”
Section: Cholesterol Contentcontrasting
confidence: 81%
“…It has been reported that the low-fat content of Kacang goat is caused by undernutrition due to traditional management systems where the goats are only fed roughage without concentrates (energy source) [61], whilst it has also been shown that the amount of nutrients consumed by the animal is influenced by the nutrient content of the feed given [62]. Kacang goat fed with fermented cocoa shell without an additional starter feed (containing high nutrients) was shown to lower the cholesterol content of the meat [63]. Furthermore, it was found that silage completely from natural grass as feed increased the contents of collagen and cholesterol in goat meat [64].…”
Section: Nutritional Properties Of Goat and Sheep Meatmentioning
confidence: 99%